Managing diabetic kidney disease. Issue 1 (5th December 2017) - Zac-Varghese, Sagen; Winocour, Peter
Abstract: Introduction: Diabetes mellitus (DM) is the leading cause of chronic kidney disease (CKD). This review covers the pillars of care essential for the management of diabetic kidney disease (DKD) including (1) early diagnosis, (2) improved glycaemic control, (3) treatment of hypertension, (4) identification and treatment of associated metabolic bone disease and (5) identification and effective management of dyslipidaemia and additional cardiovascular risk factors. Sources of data: We searched PubMed for articles using search terms: diabetic nephropathy, diabetic kidney disease, diabetes and chronic kidney disease. We used clinical guidelines from NICE, the Association of British Clinical Diabetologists (ABCD), the Joint British Societies (JBS) and the Kidney Disease: Improving Global Outcomes (KDIGO) working group. Areas of agreement: Multiple risk factor reduction targeting glycaemic control, blood pressure control, dyslipidaemia, smoking and management of obesity is important in preventing and in managing DKD. Areas of controversy: Guidelines disagree on the individualized glycaemic targets for patients with diabetic kidney disease. Growing points: The growing number of patients with DKD is causing increased pressure on limited primary care and specialized services. New ways of managing patients using novel technology solutions are required. Areas timely for development: The use of novel anti-hyperglycaemic agents, particularly sodium glucose co-transporter 2 inhibitors and GLP-1 receptor agonists, has been associated with a reduction in cardiovascular disease and DKD.